Pricing Queries (Approximately) Optimally - Syrgkanis, Vasilis; Gehrke, Johannes (2015)
Data as a commodity has always been purchased and sold. Recently, web services that are data marketplaces have emerged that match data buyers with data sellers. So far there are no guidelines how to price queries against a database. We consider the recently proposed query-based pricing framework of Koutris et al. [13] and ask the question of computing optimal input prices in this framework by formulating a buyer utility model. We establish the interesting and deep equivalence between arbitrage-freeness in the query-pricing framework and envyfreeness in pricing theory for appropriately chosen buyer valuations. Given the approximation hardness results from envy-free pricing we then develop logarithmic approximation pricing algorithms exploiting the max flow interpretation of the arbitrage-free pricing for the restricted query language proposed by [13]. We propose a novel polynomial-time logarithmic approximation pricing scheme and show that our new scheme performs better than the existing envy-free pricing algorithms instance-by-instance. We also present a faster pricing algorithm that is always greater than the existing solutions, but worse than our previous scheme. We experimentally show how our pricing algorithms perform with respect to the existing envy-free pricing algorithms and to the optimal exponentially computable solution, and our experiments show that our approximation algorithms consistently arrive at about 99% of the optimal.